2022
DOI: 10.1096/fj.202200751rr
|View full text |Cite
|
Sign up to set email alerts
|

RNA m6A reader IGF2BP3 promotes metastasis of triple‐negative breast cancer via SLIT2 repression

Abstract: Triple-negative breast cancer (TNBC) is a group of fatal malignancies characterized by high metastatic capacity, the underlying mechanisms of which remain largely elusive. We have found here that insulin-like growth factor 2 mRNA binding protein 3 (IGF2BP3) is highly expressed in TNBC and correlates clinically with distant metastasis-free survival of TNBC patients. IGF2BP3 promotes the migration and invasion capabilities of TNBC cells dependent upon cellular RNA N6-methyladenosine (m6A) modification. Mechanist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 36 publications
(113 reference statements)
1
7
0
Order By: Relevance
“…IGF2BP3 binds to and destabilizes SLIT2 m 6 A-methylated mRNA, consequently triggering the activation of canonical PI3K/AKT pathway. 45 Samanta et al 24 demonstrated that knockout of IGF2BP3 expression improved the chemosensitivity of TNBC to doxorubicin and mitoxantrone. This enhancement is attributable to the ability of IGF2BP3…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IGF2BP3 binds to and destabilizes SLIT2 m 6 A-methylated mRNA, consequently triggering the activation of canonical PI3K/AKT pathway. 45 Samanta et al 24 demonstrated that knockout of IGF2BP3 expression improved the chemosensitivity of TNBC to doxorubicin and mitoxantrone. This enhancement is attributable to the ability of IGF2BP3…”
Section: Discussionmentioning
confidence: 99%
“…As an m 6 A reader protein, IGF2BP3 can recognize and bind to mRNA transcripts targets via the m 6 A motif and regulate mRNA stabilization and translation. IGF2BP3 binds to and destabilizes SLIT2 m 6 A‐methylated mRNA, consequently triggering the activation of canonical PI3K/AKT pathway 45 . Samanta et al 24 .…”
Section: Discussionmentioning
confidence: 99%
“…m6A-binding proteins bind to the m6A methylation site. They include YT521-B homology (YTH) domain family proteins (YTHDFs), YTH domain-containing protein (YTHDCs) [ 54 ], insulin-like growth factor 2 mRNA-binding protein 3 (IGF2BPs) [ 55 ], eIF3 [ 46 , 56 , 57 , 58 ], and heterogeneous nuclear ribonucleoproteins (HNRNPs) [ 59 ]. IGF2BP2 enhances renal cell carcinoma tumorigenesis by stabilizing sphingosine-1-phosphate receptor 3 (S1PR3) mRNA [ 60 ].…”
Section: Regulators Of Rna Methylationmentioning
confidence: 99%
“…m6A regulators, such as m6A-binding proteins, can play roles in cancer initiation and progression. IGF2BP3 promoted the migration and invasion of triple negative breast cancer (TNBC) cells in an m6A modification-dependent manner [ 55 ]. IGF2BP3 bound to and destabilized the m6A-methylated mRNA of the extracellular matrix glycoprotein, slit guidance ligand 2 (SLIT2), to decrease the expression of SLIT and enhances the metastatic potential of TNBCs [ 55 ].…”
Section: Roles Of M6a-binding Proteins and M6a Demethylases In Cancermentioning
confidence: 99%
See 1 more Smart Citation